PENGARUH COMPUTATIONAL THINKING MELALUI PENDEKATAN STEM BERBANTUAN SOAL TIPE ASESMEN KOMPETENSI MINIMUM TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA - Sa’diyah, Ismiyatun; Eminita, Viarti (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research was motivated by the low level of students' mathematical literacy skills, this was due to students not being used to working on questions that could improve their mathematical literacy skills. The aim of the research is to describe the application and influence of computational thinking (CT) through a STEM approach on students' mathematical literacy abilities with the help of Minimum Competency Assessment (AKM) type questions in Statistics material. This research is included in the quasi-experimental type of quantitative research with a posttest only control design. The population in this study was all class XI SMA PGRI 3 Jakarta, totaling 66 students. The sampling technique used was simple random sampling and a sample of 59 students were obtained from two classes, namely class XI.1 as the experimental class and XI.2 as the control class. The application of computational thinking through the STEM approach in experimental classes is carried out by applying computational thinking and STEM components to learning, namely abstraction, decomposition, generalization and algorithms in the process of solving a problem. The STEM approach is located in the context of problems in the form of science, the use of technology in learning, and mathematical concepts. As well as using AKM type questions as practice questions to improve mathematical literacy skills. Based on the results of parametric statistical calculations with the t test using a mathematical literacy ability description test instrument, the value obtained is  t_count (2,509)t_tabel (2.003), where  is rejected and  is accepted, which means that computational thinking through the STEM approach assisted by AKM type questions has an effect on mathematical literacy ability. student